2011
DOI: 10.1161/hypertensionaha.111.174409
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Slow Wave Sleep Increases Risk of Developing Hypertension in Elderly Men

Abstract: The importance of sleep to health and cardiovascular disease has become increasingly apparent. Sleep disordered breathing (SDB), sleep duration, and sleep architecture may all influence metabolism and neurohormonal systems, yet no prior study has evaluated these sleep characteristics concurrently in relation to incident hypertension. Our objective was to determine if incident hypertension is associated with polysomnography (PSG) measures of SDB, sleep duration, and sleep architecture in older men. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(120 citation statements)
references
References 33 publications
7
107
2
4
Order By: Relevance
“…Recently, Fung and coworkers examined 853 community dwelling men aged 75 years and older participating in the Osteoporotic Fractures Men Study (MrOS), and found that total sleep time and other sleep measurements assessed by actigraphy were not associated with incident hypertension. 19 In our cohort of non-insomniac elderly, we found that short sleep duration < 6 h and poor sleep quality, i.e., PSQI > 5, do not affect the presence of HT or diurnal and nocturnal BP values. Moreover, no association was found between age, nocturnal blood pressure values, and reported sleep measurements such as sleep latency and sleep efficiency, apart from subjective total sleep duration.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Recently, Fung and coworkers examined 853 community dwelling men aged 75 years and older participating in the Osteoporotic Fractures Men Study (MrOS), and found that total sleep time and other sleep measurements assessed by actigraphy were not associated with incident hypertension. 19 In our cohort of non-insomniac elderly, we found that short sleep duration < 6 h and poor sleep quality, i.e., PSQI > 5, do not affect the presence of HT or diurnal and nocturnal BP values. Moreover, no association was found between age, nocturnal blood pressure values, and reported sleep measurements such as sleep latency and sleep efficiency, apart from subjective total sleep duration.…”
Section: Discussionmentioning
confidence: 63%
“…16 However, in the Gangwisch study of 4,810 participants of the NHANES cohort, a self-reported sleep duration < 5 h per night was associated with a signifi cantly increased risk of developing HT at follow-up in middle-aged subjects, but not in subjects aged > 60 years. 17 Therefore, while many epidemiological studies have suggested a relationship between sleep duration and HT in middleaged insomnia patients, the results are confl icting in the elderly population, with some studies stressing the independent risk of short sleep for HT 13,[18][19][20][21] and other studies fi nding no association. [22][23][24][25][26] The discrepancies among these reports likely stem…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…Specifically, REM sleep expression was found to be inversely related to central obesity, and SWS expression was also found to be inversely related to BMI and incident hypertension. [35][36][37] PSG measures are important to document in obesity and OSA studies, as work done by our lab 38 and others 39 indicates a role of sleep architecture in influencing metabolism and body weight regulation. The percentage of SWS and REM sleep was negatively correlated with next-day intakes of fat and carbohydrates when participants were given an ad libitum eating opportunity.…”
Section: Discussionmentioning
confidence: 91%
“…Decreased SWS is associated with a 1.8‐fold increased risk of developing hypertension in elderly men (Fung et al, 2011). The circadian rhythm of BP is blunted in patients with insomnia, even in those who are normotensive (Lanfranchi et al, 2009).…”
Section: Melatonin In the Treatment Of Circadian Rhythm And Sleep Dismentioning
confidence: 99%